1995
DOI: 10.1093/hmg/4.9.1493
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of glutaryl-CoA dehydrogenase cDNA, and expression of wild type and mutant enzymes in Escherichia coli

Abstract: We have cloned, sequenced, and expressed cDNAs encoding wild type human glutaryl-CoA dehydrogenase subunit, and have expressed a mutant enzyme found in a patient with glutaric acidemia type I. The mutant protein is expressed at the same level as the wild type in Escherichia coli, but has less than 1% of the activity of wild-type dehydrogenase. We also present evidence that the glutaryl-CoA dehydrogenase transcript is alternatively spliced in human fibroblasts and liver; the alternatively spliced mRNA, when exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 0 publications
1
47
0
2
Order By: Relevance
“…Previous structural and enzymatic studies of GCDH have repeatedly demonstrated FAD to be a tightly bound cofactor for this enzyme. Human GCDH recombinantly expressed and purified in another laboratory by methods similar to those used here revealed FAD bound in the crystal structure, although FAD had not been explicitly added at any stage (Dwyer et al, 2000;Goodman et al, 1995;Fu et al, 2004). Biochemical efforts to remove FAD from Pseudomonas fluorescens GCDH in another laboratory required multiple acid-ammonium precipitation steps, generating a very unstable protein which lost all activity if FAD was not added back within minutes (Gomes et al, 1981).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Previous structural and enzymatic studies of GCDH have repeatedly demonstrated FAD to be a tightly bound cofactor for this enzyme. Human GCDH recombinantly expressed and purified in another laboratory by methods similar to those used here revealed FAD bound in the crystal structure, although FAD had not been explicitly added at any stage (Dwyer et al, 2000;Goodman et al, 1995;Fu et al, 2004). Biochemical efforts to remove FAD from Pseudomonas fluorescens GCDH in another laboratory required multiple acid-ammonium precipitation steps, generating a very unstable protein which lost all activity if FAD was not added back within minutes (Gomes et al, 1981).…”
Section: Discussionmentioning
confidence: 88%
“…Glutaryl-CoA dehydrogenase (GCDH) is an acyl-CoA dehydrogenase (ACDH) which catalyzes an intermediate step in the metabolic breakdown of lysine and tryptophan (Gomes et al, 1981;Kim & Miura, 2004;Lenich & Goodman, 1986;Goodman et al, 1995). Unlike other flavoproteins within this family, GCDH (EC 1.3.99.7) performs , -dehydrogenation as well as decarboxylation of its substrate glutaryl-CoA to yield the product crotonyl-CoA (Dwyer et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these dehydrogenases, e.g. medium chain acyl-CoA dehydrogenase (MCAD), are involved in ␀-oxidation of fatty acids (19), whereas others, including glutaryl-CoA dehydrogenase (GCDH) and isovalerylCoA dehydrogenase, are involved in the oxidation of amino acids (20,21). Yet another group is involved in oxidative reactions in the pathway for degradation of choline to glycine, resulting in the transfer of one-carbon moieties.…”
mentioning
confidence: 99%
“…A new ACD has been identified recently (ACAD9) that is also active against long chain acyl-CoA substrates (16). Isovaleryl-CoA dehydrogenase (IVD), short/branched chain acyl-CoA dehydrogenase (SBCAD, also known as 2-methyl branched chain acyl-CoA dehydrogenase), and isobutyryl-CoA dehydrogenase (IBD) catalyze the third step in leucine, isoleucine, and valine metabolism, respectively (2-4, 11, 12, 17, 18), whereas glutaryl-CoA dehydrogenase is active in lysine metabolism (19).…”
mentioning
confidence: 99%